The Content of Local Wisdom in Traditional Expressions: Revealing the Characteristics of Jambi Malay Community - Warni, Warni; Afria, Rengki (Lembaga penelitian dan pengabdian kepada Masyarakat, 2023)
This study aims to describe the content of local wisdom in traditional expressions to reveal the characteristics of the Malay community of Jambi. The data include traditional expressions that include phrases in the form of seloko, petitih proverbs, figurative language, and proverbs. The research method uses the method of listening, note -taking and recording techniques. Data analysis using independent techniques Based on the results of the study, it was concluded that the traditional Malay expressions of Jambi, obtained either in the form of proverbs, sayings, and parables. The Malay community of Jambi in general is not open in speaking, so they use allusions to convey the message in the speech. Some of the characters of the Jambi Malay society in the traditional are heavy, religious, honest, polite, polite, wise, open, diligent, mutual aid, loyal, empathetic, humble, obedient, friendly, knightly, unyielding, democracy, tolerance, pluralism, fair, responsibility. Jambi Malay traditional expressions have a function in social life in the community. The function is as a means of community education, advice, and cultural treasures of the oral traditionKeywords: local wisdom; traditional expression; characteristic; Jambi Malay